Directions for educational development in the Year of the Teacher and Tutor - Veriaskina A. N., Sabodina E. P., Dzokaeva Z. M., Pokhilko A. D., Gubanova M. A., Sian I., Vlasova S. A., Dormidontov R. A., Omarov O. M., Ismailov S. O., Annaev R. I., Narykova O. N., Liakhova E. G., Sudakov D. V., Sudakov O. V., Gordeeva O. I., Sych G. V., Petrova N. G., Pogosian S. G., Zaritskaia V. V., Koreneva A. V., Ryzhkova I. V., Denisova O. A., Lekhanova O. L., Gudina T. V., Glukhova O. A., Bukin D. A., Zinin S. V., Tkachenko I. S., Panteleeva N. G. (Directions for educational development in the Year of the Teacher and Tutor, 2023)
the chapter presents the results of a comparative analysis of the publication activity of the teaching staff of the departments of the Faculty of Physical Education of Dagestan State Pedagogical University. The obtained research results are based on the scientometric database of the RSCI. According to a set of hetero-geneous scientometric indicators: the number of publications, the citation index, the Hirsch index, the impact factor and the categories of journals in the List of the Higher Attestation Commission in which articles are published, the authors have compiled ratings of departments, an integrated assessment of their publication productivity is given. The importance of research related to the publication activity of higher school teachers is emphasized: the study of the publication activity of teachers and structural units of the university allows not only to assess the current situation of the effectiveness of research activities, but also assumes its informational value in solving the tasks of improving the efficiency of planning and organization of scientific work of departments (faculties), in order to increase the competitiveness of the university.
Keywords: сравнительный анализ; comparative analysis; наукометрические показатели; scientometric indicators; публикационная активность; рейтинг кафедр; publication activity; rating of departments